Manajemen Tatakelola BUMDES: Mengelola Pemasaran Produk - Andi Yulianto; Mukson Mukson; Otong Saeful Bachri; Slamet Bambang Riono; Yenny Ernitawati (JAMU : Jurnal Abdi Masyarakat UMUS, 2020)
In its work in Jatimakmur Village, Songom District, Brebes, already has a BUMDes "Go Public", but BUMDes has a myriad of problems. BUMDes management can be said to be difficult because of problems such as limited human resources (HR). Some challenges faced in the management of BUMDes "Go Public" include the problem of organizational arrangements. Finding and developing village potential Marketing problems. The purpose of this activity is to encourage BUMDes managers to be able to develop marketing strategies with the right process. Encourage BUMDes managers to have the ability to identify their potential and opportunities to become profitable business units for villages by marketing their products to consumers.The stages of the implementation of community service are the identification of problems BUMDes managers, presentation of material and questions and answers with BUMDes managers. The knowledge and understanding of BUMDes managers is increasing about marketing strategies for BUMDes products. This can be seen from the indicators. Many questions from BUMDes managers submitted and explanations related to them, there is a good transfer of information and an increase in understanding related to how to market BUMDes products.